2017
DOI: 10.1186/s13148-017-0342-6
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic assays for chemical biology and drug discovery

Abstract: The implication of epigenetic abnormalities in many diseases and the approval of a number of compounds that modulate specific epigenetic targets in a therapeutically relevant manner in cancer specifically confirms that some of these targets are druggable by small molecules. Furthermore, a number of compounds are currently in clinical trials for other diseases including cardiovascular, neurological and metabolic disorders. Despite these advances, the approved treatments for cancer only extend progression-free s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 193 publications
(176 reference statements)
1
15
0
2
Order By: Relevance
“…It is likely that the increased binding affinity of the longer peptide ligand to the longer reader domain scaffold in our study may contribute to the higher IC 50 values obtained. Indeed, it is well reported that the binding and catalytic activities change with different protein construct length and domain architecture,32 as demonstrated for the KDM5A and the KDM7 subfamilies in this study. Thus, while isolated protein domains and peptide fragments provide useful information, more work with full length proteins and nucleosomes are likely needed for robust evaluation of small-molecule interactions.…”
Section: Discussionsupporting
confidence: 73%
“…It is likely that the increased binding affinity of the longer peptide ligand to the longer reader domain scaffold in our study may contribute to the higher IC 50 values obtained. Indeed, it is well reported that the binding and catalytic activities change with different protein construct length and domain architecture,32 as demonstrated for the KDM5A and the KDM7 subfamilies in this study. Thus, while isolated protein domains and peptide fragments provide useful information, more work with full length proteins and nucleosomes are likely needed for robust evaluation of small-molecule interactions.…”
Section: Discussionsupporting
confidence: 73%
“…Selection of the most appropriate druggable target with functional impact on the disease is undoubtedly a high relevant consideration. Next to rational chemical medicinal engineering approaches, biological approaches (protein complexes or cells) are essential to identify the functional effects of inhibiting particular enzymes or even isoforms [87, 88]. The EU H2020 COST Action consortium CM1406 (www.EpiChemBio.eu) brought together scientists from the different fields (chemistry, biology, medicine) to address such complex issues.…”
Section: The Fourth Wave Of Epigenetic Drug Discovery: Crystal Ball Gmentioning
confidence: 99%
“…В связи с этим интегральную оценку эпигенетической активности ксенобиотиков получают, проводя комплексный анализ влияния ксенобиотиков с использованием методов оценки отдельных механизмов эпигенетической регуляции. Наиболее удобными методами для выявления эпигенетически активных ксенобиотиков являются скрининговые тесты in vitro, способные качественно оценить эпигенетические изменения и обладающие высокой пропускной способностью [71]. С помощью таких тестов можно проанализировать более 30 соединений в одном эксперименте.…”
Section: обзорные статьиunclassified
“…Затем биотиновые метки гибридизуются со стрептавидиновыми (донорными) шариками. При лазерном облучении (680 нм) донорных шариков выделяются короткоживущие молекулы синглетного кислорода, которые взаимодействуют с акцепторными шариками, находящимися в непосредственной близости, при этом испускается усиленный хемилюминесцентный сигнал, детектируемый при 615 нм [71].…”
Section: обзорные статьиunclassified